EFEKTIVITAS PELAKSANAAN PROGRAM PENYULUHAN PERTANIAN DALAM BUDIDAYA LADA DI DESA BOU KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Ramadani, Fitri; Arimbawa, Putu; Arif, La Ode Kasno (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
This study aims to determine the effectiveness of the implementation of an extension program in pepper cultivation in Bou Village, Lambandia Subdistrict, East Kolaka Regency. The population in this study consists of all pepper farmers actively involved in the agricultural extension program in Bou Village, totaling 20 individuals. Due to the relatively small population size, the entire population was used as the sample using a saturated sampling technique (census). The analysis method employed was descriptive analysis, assisted by an effectiveness formula. The results of the study indicate that the effectiveness of the implementation of the extension program in pepper cultivation in Bou Village falls into the category of moderately effective, as assessed from three main aspects: inputs, processes, and outputs.